A retrospective study on post-arrival mortality rate of Australian boer goats in a breeder farm in Malaysia - Salisi, Mohd Shahrom; Saad, Mohd Zamri (Universiti Putra Malaysia Press, 2012)
Post-arrival mortality pattern and the causes of those mortalities were studied in a Boer goat breeding farm in Malaysia. The farm was established in October 2005, following an importation of 597 breeder Boer goats from Australia. Further importations of 534 Boer goats were made in July 2007, and 166 goats in March 2008. Farm records covering the period between October 2005 and December 2008 were analyzed for monthly mortality pattern with special attention on the post-arrival weeks. Upon arrival, goats were provided with vitamins, anti-stress and antibiotic cover. They were fed with cut grasses and supplemented with goat pellets at 350g/goat/day. Drinking water was also available ad libitum. During the study period of 2005 to 2008, there were significantly (p<0.05) higher rates of annual mortality during rainy months (7%-14%) as compared to dry months (2%- 5%). Meanwhile, the post-arrival mortality showed an average of 27%, ranging between 13% and 43%, of the Boer goats died during the first 6 weeks of post-arrival. In particular, the goats arriving in the rainy months of October 2005 and March 2008 showed higher post-arrival mortality than those arriving in the dry month of July 2007. The post-arrival mortality pattern revealed a gradual but significant (p<0.05) increase as early as week 1, with an average of 5% mortality to reach peak at week 3 with 35% mortality before it gradually decreased to 6% at week 6 and 3% at week 7. The major causes of post-arrival mortalities were pneumonic mannheimiosis and helminthiasis, which were associated with the stresses of handling, loading and unloading during shipment.